STUDIES ON THE CURRENT LEVEL OF INVESTMENTS FUNDED BY THE NATIONAL RURAL DEVELOPMENT PROGRAM FOR MEAT PROCESSING IN THE DEVELOPMENT CENTER REGION - Daniel Valeriu ULIU; Marius VLADU (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The National Rural Development Program is a program coordinated by the Ministry of Agriculture and Rural Development, in consultation with representatives of bodies, organizations and social partners active in this field and approved following consultations with the European Commission, which provides European non-reimbursable funds for investments private and public projects that ensure the development of rural areas in Romania. Sub-measure 4.2. - "Support for investment in the processing / marketing and / or development of agricultural products", falls within measure 4 - Investments in physical assets. It is necessary to concentrate support for investments in modern production spaces and technologies, the development of new products, the application of innovative practices and technologies in the meat industry The main purpose of this paper is an analysis of the investments with European funds regarding the development of meat processing in the Region of the Development Center of Romania in the period 2015-2017. In this paper, we propose to follow the influence of support under sub-measure 4.2 on the dynamics of investments in meat processing, at the level of the Centre Region, which have an eligible value of 14,837,922 euros, and the public value is 6,482,196 euros, in relation to nationally funded projects with an eligible value of 70,435,100 euros and a public value of 32,501,225 euros and a number of 30 projects.